Franklin in the Dark - Bourgeois, Paulette; Clarke, Brenda (Toronto : Kids Can Press, 1987)
Summary A turtle afraid of small dark places, and therefore of crawling into his shell, asks a variety of animals for advice, only to find out that each has a fear of its own.
Big book with easel can be used with a group of up to eight beginning readers in a shared reading approach.
Keywords: Reading (Primary).; Okuma (İlköğretim).